Lipopolysaccharide administration for a mouse model of cerebellar ataxia with neuroinflammation - Hong, Jungwan (Sci Rep, 2020)
Most cerebellar ataxias (CAs) are incurable neurological disorders, resulting in a lack of voluntary control by inflamed or damaged cerebellum. Although CA can be either directly or indirectly related to cerebellar inflammation, there is no suitable animal model of CA with neuroinflammation. In this study, we evaluated the utility of an intracerebellar injection of lipopolysaccharide (LPS) to generate an animal model of inflammatory CA. We observed that LPS administration induced the expression of pro-inflammatory molecules following activation of glial cells. In addition, the administration of LPS resulted in apoptotic Purkinje cell death and induced abnormal locomotor activities, such as impaired motor coordination and abnormal hindlimb clasping posture. Our results suggest that intracerebellar LPS administration in experimental animals may be useful for studying the inflammatory component of CA.